Children’s Evaluations About Lying for Prosocial and Antisocial Reasons - Muhammed Şükrü Aydın; Sema Karakelle (İnsan & Toplum)
Children’s reasoning and evaluations about lying have been the subject of much research during the past two decades. However, these studies are seen to have been carried out in a limited number of countries. Therefore, the present study examines the evaluations of Turkish children between the ages of 4 and 8 regarding prosocial and antisocial lies. The study uses picture cards to present the children with vignettes in which a protagonist lies for their own or others’ benefit. The results show that children found telling lies to be more acceptable in the context of prosocial stories, with prosocial lies being found to be more acceptable among 8-year-old children compared to 4- and 5-year-old children. Due to this research having been pioneering in a different country, the study discusses the findings through intracultural and intercultural factors.